2006
DOI: 10.1007/s10803-006-0170-6
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Motor Delays in Young Children: Autism Spectrum Disorder, Developmental Delay, and Developmental Concerns

Abstract: This study assessed motor delay in young children 21-41 months of age with autism spectrum disorder (ASD), and compared motor scores in children with ASD to those of children without ASD. Fifty-six children (42 boys, 14 girls) were in three groups: children with ASD, children with developmental delay (DD), and children with developmental concerns without motor delay. Descriptive analysis showed all children with ASD had delays in gross motor skills, fine motor skills, or both. Children with ASD and children wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
216
2
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 357 publications
(257 citation statements)
references
References 17 publications
11
216
2
13
Order By: Relevance
“…Some of such studies confirmed this claim by comparing the scores of Peabody test and Bayley test in children with autism and their typical peers. The result showed significant delay and differences in gross and fine motor skills in ASD children in comparison to the control group [10].…”
Section: Introductionmentioning
confidence: 86%
“…Some of such studies confirmed this claim by comparing the scores of Peabody test and Bayley test in children with autism and their typical peers. The result showed significant delay and differences in gross and fine motor skills in ASD children in comparison to the control group [10].…”
Section: Introductionmentioning
confidence: 86%
“…For example, no differences in running, jumping, throwing, catching, and balance were found between children with autism and those with mental retardation in a study by Morin and Reid (1985). A more recent study found no differences between children with autism 21-41 months of age and children with general developmental delays in reflexes, balance, locomotion, grasping, object manipulation, or visual-motor integration (Provost et al 2006). Similarly, Rogers and colleagues did not find differences in fine motor maturity or motor planning in 2-year-olds with autism compared to developmentally matched typical and atypical groups (Rogers et al 2003).…”
Section: Introductionmentioning
confidence: 92%
“…Most studies have focused on older children with autism. The only studies of preschool-aged children provide mixed results, with one documenting gross and fine motor deficits relative to typical controls but not mental-age matched controls with developmental delays (Provost et al 2006) and the other finding no differences relative to either group (Rogers et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Peabody Developmental Motor Scale is considered as a reliable and valid tool used to evaluate fine motor skills performed by preschool children [15]. Sensory integration approach is one of the interventions that commonly and positively affect the rehabilitation of autistic children [16,17].…”
Section: Discussionmentioning
confidence: 99%